Afectos cotidianos en Los días azules y La virgen de los sicarios de Fernando Vallejo - López Rico, Natalia; Nitschack, Horst (Studia Romanica Posnaniensia, 2024)
This article analyzes the relationship between affects and everyday life in two novels by the Colombian writer Fernando Vallejo (b. 1942), Los días azules (1985) and La virgen de los sicarios (1994). While the first novel portrays forces of affective dynamics such as joy, compassion, and hope that still guide social practices in everyday life, in La virgen de los sicarios these forces disappear and are replaced by hatred, rage, and violence. Consequently, both affects and everyday life undergo a transformation, proving to be, above all, a permanent field of conflict and tensions.